2016
DOI: 10.1111/jocn.13239
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of effective de‐escalation in acute inpatient psychiatric settings

Abstract: These findings provide support for de-escalation in practice but suggest that nurses may lack confidence in using the technique when the risk of violence is greater. Providing evidence-based staff training may improve staff confidence in the use of this potentially powerful technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 27 publications
0
33
0
5
Order By: Relevance
“…81 An analysis of the CONSEQ data, 3 obtained during the first 2 weeks of a hospital admission for 522 randomly sampled patients, showed that 60% of uses of de-escalation were successful, although de-escalation was less likely to be successful with patients who had a history of violence. 82 Research into de-escalation is at an early stage; current evidence suggests that it can be effective and therefore could to some degree act as a substitute for PICU care.…”
Section: Seclusion As An Alternative To Psychiatric Intensive Care Unmentioning
confidence: 99%
“…81 An analysis of the CONSEQ data, 3 obtained during the first 2 weeks of a hospital admission for 522 randomly sampled patients, showed that 60% of uses of de-escalation were successful, although de-escalation was less likely to be successful with patients who had a history of violence. 82 Research into de-escalation is at an early stage; current evidence suggests that it can be effective and therefore could to some degree act as a substitute for PICU care.…”
Section: Seclusion As An Alternative To Psychiatric Intensive Care Unmentioning
confidence: 99%
“…However, study designs limit findings to binary outcomes (i.e. de‐escalation success or failure) and they do not reveal factors contributing to either outcome (Bowers et al., ; Lavelle et al., ). Qualitative research investigating the range of staff, patient and environmental factors contributing to de‐escalation outcome has been recommended (Lavelle et al., ; Price & Baker, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many patients have a complex mix of overlapping layers, and with just under 20% of the populace living with a mental illness, one of the layers may be psychiatric in nature (Centers for Disease Control and Prevention, 2014;Unsworth, McKeever, & Kelleher, 2012). Early assessment of agitation, and early intervention utilizing de-escalation skills will assist the patient to feel supported, knowing the student nurse will help the patient to maintain control of themselves (Cowin et al, 2003;Lavell, Stewart, James, Richardson, Renwick, Brennan, & Bowers, 2016). This therapeutic process can have an immediate effect of putting the patient at ease, and therefore useful for patients, with a calming effect on medical conditions.…”
Section: Significance Of the Projectmentioning
confidence: 99%
“…The nursing profession will benefit from the student nurse learning verbal de-escalation skills and becoming confident in their use (Lavell et al, 2016). As future nurses, the rates of injury and loss of work productivity should be less, as the patient's agitation will be recognized and treated early (Simon & Hurvitz, 2014).…”
Section: Significance Of the Projectmentioning
confidence: 99%